(untitled) (Informatica, 2024)
The aim of this work is to develop a dynamic coding strategy for a Multi user MIMO NOMA 5G downlink communication by means of concatenation of coding methods. The ultimate motive behind 5G technology is to deliver data at a ultra-high speed of multi - Gbps rate with extremely low latency, being highly reliable, offering huge network capacity, readily available channels and a much stable user experience accommodating multiple simultaneous users. This in turn demands a highly flexible and an effective channel coding method as it helps out the communication to be almost error free by reducing the bit errors of the transmitted data by saving it from the channel noise and the available interference in the channel. This paper provides an efficient approach based on the concatenation of Polar codes that is suited for a multi user mimo NOMA system that meets the criteria of the 5G standard. To compare the performance of mimo NOMA systems with that of concatenated PDCCH (Physical Downlink Control CHannel) polar codes (Symbol Energy to Noise Ratio) versus BLER (BLock Error Rate) simulations have been performed. The results show that the suggested approach performs better in terms of Sum Rate Capacity versus SNR in multiuser mimo NOMA system.